Phytochemical Characterization and Therapeutic Potential of Catechin in the Treatment of Urinary Tract Infections - Kumar, Avinash; Chandel, Neha (Journal of Neonatal Surgery, 2025)
Background: Urinary Tract Infections (UTIs) are a prevalent global health concern, often caused by bacterial pathogens such as Escherichia coli. Investigating natural substances for their potential as a treatment for UTIs has gained popularity in recent years. Methods: This research focuses on the phytochemical characterization of Tea leaf extracts and the specific emphasis on catechin, a flavonoid known for its potent antioxidant and antimicrobial properties. Result/Conclusions: The paper provides an in-depth analysis of the existing literature on the subject, highlighting the potential of catechin as a novel and effective treatment for UTIs.